2019
DOI: 10.1111/bcp.13865
|View full text |Cite
|
Sign up to set email alerts
|

Cefuroxime plasma and tissue concentrations in patients undergoing elective cardiac surgery: Continuous vs bolus application. A pilot study

Abstract: Aims Surgical site infections contribute to morbidity and mortality after surgery. The authors hypothesized that higher antibiotic tissue concentrations can be reached for a prolonged time span by continuous administration of prophylactic cefuroxime compared to bolus administration. Methods Twelve patients undergoing elective cardiac surgery were investigated. Group A received 1.5 g cefuroxime as bolus infusions before surgery, and 12 and 24 hours thereafter. In group B, a continuous infusion of 3.0 g cefuroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
(32 reference statements)
2
13
0
Order By: Relevance
“…Whilst routine bolus dosing appeared sufficient for prophylaxis, continuous infusion of cefuroxime was demonstrated to provide a higher percentage of ƒT > bacterial MIC 7 . Similar findings were reported by Skhirtladze‐Dworschak et al, who showed that higher cefuroxime concentrations were achieved in plasma—and importantly, subcutaneously—over a prolonged period of time when cefuroxime was administered to adult patients undergoing elective cardiac surgery via infusion rather than standard bolus dosing 8 . Finally, Rimmler et al used a physiologically based pharmacokinetic model (PK‐Sim ®/MoBi ®) to investigate unbound plasma concentrations of cefuroxime following pre‐operative administration in the context of thoracic surgery.…”
supporting
confidence: 73%
“…Whilst routine bolus dosing appeared sufficient for prophylaxis, continuous infusion of cefuroxime was demonstrated to provide a higher percentage of ƒT > bacterial MIC 7 . Similar findings were reported by Skhirtladze‐Dworschak et al, who showed that higher cefuroxime concentrations were achieved in plasma—and importantly, subcutaneously—over a prolonged period of time when cefuroxime was administered to adult patients undergoing elective cardiac surgery via infusion rather than standard bolus dosing 8 . Finally, Rimmler et al used a physiologically based pharmacokinetic model (PK‐Sim ®/MoBi ®) to investigate unbound plasma concentrations of cefuroxime following pre‐operative administration in the context of thoracic surgery.…”
supporting
confidence: 73%
“…Our pharmacokinetic/pharmacodynamic study of cefuroxime as PAP in cardiac surgery differs from several previous investigations, 27,29–32 some of which were merely descriptively without the development of a pharmacokinetic model 33–35 …”
Section: Discussionmentioning
confidence: 82%
“…In this study of cefuroxime in cardiac surgery, we used plasma concentrations taken Our PK/PD-study of cefuroxime as PAP in cardiac surgery differs from several previous investigations [27,[29][30][31][32], some of which were merely descriptively without the development of a pharmacokinetic model [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skhirtladze-Dworschaket al 28 compared antibiotic prophylaxis with cefuroxime in intermittent bolus and continuous infusion assessing their serum and subcutaneous tissue concentrations; observed higher concentrations of cefuroxime and for a longer period of time in the plasma and subcutaneous tissue, when cefuroxime was administered continuously, and concluded that its concentration measurements were higher in patients who received the antibiotic in continuous infusion.…”
Section: Discussionmentioning
confidence: 99%